Value Engineering Analysis on Building Structure (Case Study: Java Steam Power Plant 9&10 2x1000 MW Suralaya Project) - Putra, Reza Andhika; Setiono, Setiono; Fajar Sri Handayani (Indonesian Journal Publisher, 2024)
Cost is an important element in the success of a project because problems with project implementation costs can hinder the achievement of the project. Problems in project implementation related to costs can be overcome by carrying out value engineering analysis. The concept of value engineering is a systematic effort to analyze existing problems and aims to achieve the desired functions or types of work with efficient costs and optimal results. The value engineering carried out in the case study analyzed by the author is a change in the implementation of concrete work from conventional methods to precast methods to obtain cost efficiency. The method used is a data collection method and analysis method according to the value engineering analysis stages. The results of the value engineering analysis obtained by the author through creative ideas in the form of changing conventional concrete work to precast concrete are savings in work costs on building structural components in the form of slabs. The cost savings obtained were Rp695,905,059.00 or 2.21%.